Serum CA 19-9 as a good prognostic biomarker in patients with bladder cancer. (March 2015) - Wang, Qing-hai; Ji, Zhi-gang; Chen, Zhi-gang; Li, Han-zhong; Fan, Hua; Fan, Xin-rong; Shi, Bing-bing; Fang, Yujiang
Abstract: Background: Bladder cancer (BC) is the second leading malignant tumors of the genitourinary system. CA 19-9 has served as a diagnostic and prognostic marker for pancreatic carcinoma for years. In recent year, although a few studies have evaluated the roles of CA 19-9 in BC, the results are conflicting and the number of the patients studied is very small. Aim: To investigate the potential of serum CA 19-9 to serve as a diagnostic and prognostic marker of BC in a larger number of patients. Methods: A total of 272 (144 BC patients and 128 healthy subjects) were enrolled. Patients were followed-up routinely at 3-month intervals for 5 years. Serum CA 19-9 level was detected by ELISA. Results: CA 19-9 level was much higher than that in healthy subjects (43.69 ± 6.92 U/ml vs. 12.31 ± 4.39 U/ml, p < 0.001). However, when the value of 37 U/ml of serum CA 19-9 was used as the cut-off value for BC the sensitivity of CA 19-9 for BC was dropped to 38.8%. CA 19-9 was much higher in muscle invasive tumor subgroup than that in superficial tumor subgroup (38.09 ± 7.14 U/ml vs. 20.71 ± 4.15 U/ml, p < 0.027). CA 19-9 level was comparable in both subgroups (29.78 ± 5.07 U/ml vs. 26.13 ± 5.97 U/ml, p = 0.565). BC patients with more than 5 years survival time had lower serum CA 19-9 level than the rest (15.86 U/ml vs 46.68 U/ml, p < 0.001). Survival rate (>5 years) of patients with lower CA 19-9 levels (<29 U/ml) was significantly increased in comparison to those with elevated serum CA 19-9 levels (>29 U/ml) (p < 0.001). Conclusions: serum CA 19-9 is not a good diagnostic maker, but a very powerful prognostic marker for BC. Such a study might be helpful for urologists to manage patients with BC. Highlights: CA 19-9 is not a sensitive diagnostic marker for bladder cancer. CA 19-9 is associated with tumor stage, but not with tumor grade. CA19-9 is a good prognostic marker for bladder cancer.